A local index of Maritime Continent intraseasonal variability based on rain rates over the land and sea - C. L. Vincent; T. P. Lane; M. C. Wheeler (Geophysical Research Letters)
Abstract A local index for describing intraseasonal variability over the Maritime Continent is developed. The index is based on the ratio of area‐averaged rain rate over the land to that over the sea. It takes advantage of the fact that the main convective envelope of intraseasonal variability events tends to modulate the diurnal precipitation cycle over the land over the entire Maritime Continent. Lagged analysis is used to create composite intraseasonal variability events, where “day 0” is chosen according to when the normalized rain rate over the sea becomes greater than that over the land. The index identifies intraseasonal variability events associated with the Madden Julian Oscillation as well as equatorial Kelvin waves and westward propagating equatorial Rossby waves. The results suggest a similar local impact of all such events in suppressing the rain rate over land relative to that over the sea when the main convective envelope approaches.